PENGAWASAN SOSIAL TERHADAP PEREDARAN MIRAS DI PEKANBARU (STUDI PADA PEDAGANG MIRAS DI JALAN. IR H JUANDA) - Mika Mardilla; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was carried out in the city of Pekanbaru. The purpose of this study was to determine the characteristics of liquor dealers in the city of Pekanbaru. The topic of this research focus is the social control measures applied to the circulation of alcohol in the city of Pekanbaru. The technique of determining samples by purposive sampling and setting the number of samples as many as 5 people. The author uses qualitative descriptive methods and data instruments are observation, interviews and documentation. The study found that there are characteristics of liquor dealers in the city of Pekanbaru, as follows: Source of capital to sell liquor, capital to sell liquor on average obtained by the subject of research from personal savings, get a loan from relatives and friends. Distribution of Liquor for Sale, Research conducted also found that the distribution of drinks sold by research subjects came from Singapore. Sales System and Sales Time, the average research subject starts selling from 8:00 p.m. to dawn. The research also found that there were several forms of social control over liquor trade in the city of Pekanbaru, as follows: Supervision by Community Members, The study found that people around Jalan Juanda were not too concerned about alcohol trading activities by the subject of the study, as evidenced by the subject's response research that there is no community who reprimands these prohibited activities. Supervision by the Government, Research subjects said that no one received official information from relevant officials in the prohibited trading activities. Keywords: Social Monitoring, Values and Norms